THE INTEGRATION OF SCIENCE IN ISLAMIC EDUCATION: A CRITICAL ANALYSIS OF AZYUMARDI AZRA'S EDUCATIONAL THOUGHT - Prihatin, Nyimas Yunierti; Abdurrahmansyah, Abdurrahmansyah; Munir , Munir; Fauzi , Muhammad; Alimron, Alimron; Wigati , Indah (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: This study stems from the urgency of integrating science into the Islamic education system as proposed by Azyumardi Azra, particularly in response to the challenges of globalisation and technological developments. Research Objective: The objective of this study is to analyse Azra's ideas on scientific integration through various theoretical perspectives in order to assess their relevance and contribution to the development of contemporary Islamic education. Method: This study uses a qualitative method with a literature study approach, through a systematic search of Azra's works in the form of books, journals, and scientific articles, as well as relevant supporting literature. Results: The results show that Azra's concept of scientific integration emphasises the synergy between religious and general knowledge as the foundation for the modernisation of education, enabling it to respond adaptively to social change and technological advances. This idea positions education as a vehicle for shaping believers who possess intellectual and scientific competence. Thus, Azra's thinking provides a philosophical basis as well as a practical direction for the reconstruction of a progressive, open, and contextual education system without losing its Islamic identity. Conclusion: This study concludes that the integration of science is an important strategy in strengthening the role of education as a driver of scientific progress and Muslim civilisation in the modern era.